Pengelolaan Kantin Sekolah Untuk Pembelajaran Hidup Sehat dan Inspirasi Kewirausahaan - Fathurrahman Fathurrahman; Asmoni Asmoni; R. Chusnu Yuli Setyo (JAMP : Jurnal Administrasi dan Manajemen Pendidikan, 2024)
Abstract: This study reveals the experience of SMPN 3 Lamongan (Lamongan State Junior High School 3) in managing a healthy school canteen, giving entrepreneurship learning, and giving inspiration of economic activity towards both the school community and the surrounding community to cooperate in the canteen, all of which are as the Implementation of Independent Curriculum. The method of this study is designed in a qualitative approach, in which the data are collected by interview, observation, and documentation. The data are then analyzed through these steps: data condensation, data display, and conclusion drawing. The result shows that 1) the location of the canteen is beautiful and comfortable; 2) canteens are part of the implementation of the independent curriculum which is used for learning to live a healthy and clean life through the provision of nutritious, healthy and free from preservatives, dyes, sweeteners, and flavorings; 3) The canteen provides motivation and inspiration for the cultivation of students' entrepreneurial spirit. As well as collaborating with school residents and parents to provide food, snacks, and drinks with nutritious, healthy, and attractive criteria; and 4) canteens are also as a Adiwiyata School program which is implemented by the principles of environmental conservation. Keywords: school canteen, healthy behavior learning, entrepreneurial inspiration Abstrak: Penelitian ini mengungkap pengalaman SMPN 3 Lamongan dalam mengelola kantin sekolah sehat mandiri, memberikan pembelajaran kewirausahaan, dan memberikan inspirasi kegiatan ekonomi baik kepada warga sekolah maupun masyarakat sekitar untuk bekerjasama dalam kantin. yang kesemuanya merupakan Implementasi Kurikulum Mandiri. Metode penelitian ini dirancang dengan pendekatan kualitatif, dimana pengumpulan data dilakukan melalui wawancara, observasi, dan dokumentasi. Data tersebut kemudian dianalisis melalui langkah-langkah berikut: reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa 1) lokasi kantin asri dan nyaman; 2) kantin merupakan bagian dari Penerapan Kurikulum merdeka yang digunakan untuk pembelajaran hidup sehat dan bersih melalui penyediaan asupan jajanan, dan minuman yang bergizi , sehat dan bebas dari bahan pengawet, pewarna, pemanis, dan penyedap rasa,; 3) kantin memberikan motivasi dan inspirasi penanaman jiwa kewirausahaan peserta didik. Serta bekerjasama dengan warga sekolah dan wali murid untuk menyediakan makanan, jajanan, dan minuman dengan kriteria bergizi, sehat, dan menarik; dan 4) kantin juga merupakan bagian dari program sekolah Adiwiyata Sekolah yang dilaksanakan dengan memperhatikan prinsip pelestarian lingkungan hidup. Kata kunci: Kantin sekolah; Pembiasaan Hidup sehat, inspirasi kewirausahaan